NEUROLOGICAL ASSESSMENT: A SURVEY OF PAEDIATRIC NURSES’ KNOWLEDGE AND ACTIONS - Manning, Joseph (2005)
Aim The aim of this research study was to investigate whether paediatric nurses have adequate knowledge to perform a neurological assessment competently. Rationale Neurological assessment is essential in determining the neurological status of the child and what actions should be undertaken. It was evident from personal observations that an inconsistency of knowledge and actions relating to a neurological assessment existed. Methodology A quantitative methodology with a questionnaire design was used to ascertain the level of paediatric nurses’ knowledge and actions with participants from a large, general sample of paediatric nurses. Results The majority of paediatric nurses did not have adequate knowledge to underpin a neurological assessment. Knowledge positively correlated with actions, academic qualifications, and experience. Conclusion These results have highlighted that paediatric nurses need to be aware of their own knowledge deficits and require support and training in the neurological assessment of a child to bridge this gap between knowledge and actions.